2020
DOI: 10.23978/inf.99084
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of individuals as information sources among two language minorities during COVID-19 pandemic in Finland

Abstract: This article is licensed under the terms of the CC BY-NC-SA 4.0 -license

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The isolation people endured during the first and second waves of COVID‐19 has led to concerns about mental health (Ojaranta et al, 2020). One study reported that greater awareness and negative emotional responses to COVID‐19 were associated with greater media consumption (Fernandez et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The isolation people endured during the first and second waves of COVID‐19 has led to concerns about mental health (Ojaranta et al, 2020). One study reported that greater awareness and negative emotional responses to COVID‐19 were associated with greater media consumption (Fernandez et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Unlike many previously reported studies that often center more on the effects of HIB than actual HIB, in this section the focus is on people, and the research methodologies are diversified (Table 7), offering important insights into HIB during the Covid-19 crisis. Information practices emerge as collaborative or "orchestrated" and interaction in social networks, both online and offline, becomes, not only, an important information source for many, but it also appears to exert a protective function in regulating emotional responses to information about the crisis (Chivers et al, 2020;Ojaranta, Ahmadinia, & Eskola, 2020;Pan, Cui, & Qian, 2020;Tandoc & Lee, 2020). HIB and other behaviors, such as preventive practices and attitude towards vaccines, appear as conditioned and originated by relationships and roles, especially roles within the family and women's roles in sharing information through social networks (Ali, Whitebridge, Jamal, Alsafy, & Atkin, 2020;Montesi, 2020;Ojaranta et al, 2020;Xu et al, 2020).…”
Section: Information In Daily Life During Lockdown and The Effect Of ...mentioning
confidence: 99%
“…Information practices emerge as collaborative or "orchestrated" and interaction in social networks, both online and offline, becomes, not only, an important information source for many, but it also appears to exert a protective function in regulating emotional responses to information about the crisis (Chivers et al, 2020;Ojaranta, Ahmadinia, & Eskola, 2020;Pan, Cui, & Qian, 2020;Tandoc & Lee, 2020). HIB and other behaviors, such as preventive practices and attitude towards vaccines, appear as conditioned and originated by relationships and roles, especially roles within the family and women's roles in sharing information through social networks (Ali, Whitebridge, Jamal, Alsafy, & Atkin, 2020;Montesi, 2020;Ojaranta et al, 2020;Xu et al, 2020). Groups such as older persons, that may be less visible in massive analysis of web activity, are also given more visibility (Martos & Casarin, 2020).…”
Section: Information In Daily Life During Lockdown and The Effect Of ...mentioning
confidence: 99%
See 2 more Smart Citations